Experiencing Loneliness in Adolescence: A Matter of Individual Characteristics, Negative Peer Experiences, or Both?. Issue 1 (2nd April 2013) - Vanhalst, Janne; Luyckx, Koen; Goossens, Luc
Abstract The present study builds on the child‐by‐environment model and examines the joint contribution of intra‐individual characteristics (i.e., self‐esteem and shyness) and peer experiences (i.e., social acceptance, victimization, friendship quantity, and friendship quality) in the association with loneliness. A total of 884 adolescents (Mage= 15.80; 68 percent female) participated in this multi‐informant study. Results indicated that, in addition to self‐esteem and shyness, being poorly accepted by peers, being victimized, lacking friends, and experiencing poor‐quality friendships each contributed independently to the experience of loneliness. Further, friendship quantity and quality mediated the relation between the two intra‐individual characteristics and loneliness. Finally, a significant interaction was found between self‐esteem and social acceptance in predicting loneliness. The present study highlights the importance of investigating the joint effects of inter‐individual experiences and intra‐individual characteristics in examining loneliness. Suggestions to elaborate the child‐by‐environment model in loneliness research are discussed, and clinical implications are outlined.